Narrative form and consciousness. - Muhammad Firdaus Isnin. (2011)
Can a novel exhibit signs of consciousness? If so, how does a writer express such characteristics? With a specific look at Beckett's Trilogy of novels, this paper delves into the treatment of language and the purifying process which Beckett puts it through. Already aware of the Saussurean signifier/signified limitation, Beckett's use of language appears unburdened by not allowing itself to express its deficiency. Going beyond the sphere of rudimentary semiotics, Beckett's language is an elaborate experiment in form which creates a work that is aesthetically pleasing. The pure impulse to create objects of beauty is the mark of an artist and Beckett's prose is evidence of the energy and completeness of movement which all objects of beauty have in common.